Idea jakości życia społecznego w klasycznej i współczesnej myśli europejskiej – na marginesie książki „Błąd pomiaru. Dlaczego PKB nie wystarcza” - Drabińska, Danuta (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
The paper discusses the idea of quality of social life in classical and contemporary European thought. It was inspired by Mismeasuring our lives: Why GDP doesn’t add up by J.E. Stiglitz, J.-P. Fitoussi and A. Sen – a book that is a report on existential condition of contemporary societies in the context of civilizational changes. The paper also discusses the idea of permanent self-sustaining development, relations between economic activity and social welfare, and methods used to measure quality of life. Contemporary context of discussion was confronted with classics of economic thought. The conclusion contains analysis of contemporary dimension of moral philosophy. In this context the quality of life seems as important as economic growth.